2010
DOI: 10.1088/1468-6996/11/4/044305
|View full text |Cite
|
Sign up to set email alerts
|

Present status of amorphous In–Ga–Zn–O thin-film transistors

Abstract: The present status and recent research results on amorphous oxide semiconductors (AOSs) and their thin-film transistors (TFTs) are reviewed. AOSs represented by amorphous In-Ga-Zn-O (a-IGZO) are expected to be the channel material of TFTs in next-generation flat-panel displays because a-IGZO TFTs satisfy almost all the requirements for organic light-emitting-diode displays, large and fast liquid crystal and three-dimensional (3D) displays, which cannot be satisfied using conventional silicon and organic TFTs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
1,192
3
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,746 publications
(1,220 citation statements)
references
References 131 publications
22
1,192
3
3
Order By: Relevance
“…[1][2][3][4][5] A notable characteristic of amorphous oxides, relative to their crystalline counterparts, is that these materials contain structural disorder-related defects (for example, free volume) in addition to non-stoichiometric defects (for example, oxygen vacancies), which significantly affect the corresponding electrical properties. 3,[6][7][8] Moreover, the degree of structural disorder in amorphous metal oxides is always likely to decrease to form more stable structures because internal atomic rearrangement occurs even below the glass transition temperature (T g ). This process is known as structural relaxation (SR) [9][10][11] and results in continuous changes in the electrical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] A notable characteristic of amorphous oxides, relative to their crystalline counterparts, is that these materials contain structural disorder-related defects (for example, free volume) in addition to non-stoichiometric defects (for example, oxygen vacancies), which significantly affect the corresponding electrical properties. 3,[6][7][8] Moreover, the degree of structural disorder in amorphous metal oxides is always likely to decrease to form more stable structures because internal atomic rearrangement occurs even below the glass transition temperature (T g ). This process is known as structural relaxation (SR) [9][10][11] and results in continuous changes in the electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 These results indicate that oxygen vacancies (V O s), which are inherent chemical defects, act as the dominant electron donors. Interestingly, the V O s can act as deep donors 8 (that is, limited donation of free electrons), electron traps 3,6 and shallow donors, whose electronic states are determined by the local atomic environment. Certain researchers have suggested that all V O s in crystalline IGZO are deep donors; however, certain V O s act as shallow donors in a-IGZO when the structural disorder causes weak interactions between the metal ions and V O s (that is, when the bonding distance between a metal ion and a V O increases, called outward relaxation).…”
Section: Introductionmentioning
confidence: 99%
“…Indium (In)-based amorphous oxide semiconductors are considered as a promising material for next-generation thin-film electronics and optoelectronics because they have high electron mobility, transparency, flexibility and uniformity. [29][30][31][32][33] However, the success of these applications has been limited by the lack of stability in their electrical properties owing to charge trapping.Investigation of the charge-trapping defects on the atomic scale is an essential prerequisite to overcome the instability issue of the indiumbased amorphous oxide semiconductors. An oxygen-vacancy (V O ) defect has been suggested as a metastable hole-trap center.…”
mentioning
confidence: 99%
“…), high frame rate (>240 Hz), and three-dimensional (3D) displays. In order to realize such highend products such as 3D televisions that do not require specialized glasses, using either active matrix liquid crystal displays (AMLCDs) or active-matrix, organic light-emittingdiode (AMOLED) panels, high-performance thin film transistor (TFT) devices acting as switching or driving elements are [12,150]. For example, for large AMOLED TVs, the mobility requirement is generally predicted to be over 30 cm 2 /V · s (depending on display resolution and pixel-circuit designs) because OLED pixels need high current in order to emit light through current injection.…”
Section: Demand For Higher Mobilitymentioning
confidence: 99%
“…They have since been taking the place of a-Si and LTPS, given several key qualities, including high electrical mobility, amorphicity, and high optical transparency. Moreover, AOSs have a lower density-of-states (DOS), including tail and deep level states, compared to that of a-Si, resulting in superior electrical stability [12].…”
Section: Introductionmentioning
confidence: 99%